EFEKTIVITAS PRENATAL YOGA TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PMB RINA DAN PMB IDA KOTA DEPOK - Girsang, Rut Yohana (Politeknik Tiara Bunda, 2022)
Background : Back pain discomfort is often experienced in pregnant women in the III trimester. Doing prenatal yoga is one of the non-pharmacological therapies. Research objectives: To find out the differences before and after prenatal yoga against back pain of pregnant women in the III trimester at the PMB Rina dan PMB Ida Kota Depok . Research Methods: This type of research is pre-experiential with a pre-test group design and a post-test design. The population in this study was all III trimester pregnant women at the PMB Rina dan PMB Ida Kota Depok, which met 33 pregnant women. The sempel retrieval technique is a total sempel with inclusion and exclusion criteria. Data processing uses editing, coding, entery data, scoring, tabulating, with statistical test data analysis of ujiwilcoxon. The results of the study: Before doing prenatal yoga, a total of 19 respondents (57.6%) experienced back pain on a scale of 4 (severe pain), 9 respondents (27.3%) experienced back pain on a scale of 5 (uncontrolled pain). After doing prenatal yoga, the discomfort of back pain mostly decreased, namely 28 respondents (84.5 %). statistical tests of the lcoxon test showed a ρ value of 0,000 < α 0,05. Conclusion: H1 is accepted, meaning that there is an influence of prenatal yoga on the decrease in back pain in pregnant women in the III trimester.